Obstetric Risk Factors for Low Birth Weight Amongst Full Term Babies Born at A Tertiary Care Hospital of Belgaum District, South India - Damaru Prasad Paneru; Vijaya A Naik; B R Nilgar; Mahesh D Mallapur (Medsci Publications, 2014)
Introduction: Low Birth Weight is a multifaceted socio- medical and public health problem, especially in developing countries where Intrauterine Growth Retardation remains major manifestation. This study was carried out to identify obstetric risk factors for Low Birth Weight amongst full term babies born at a tertiary care hospital. Methodology: This was the retrospective record-based study, carried out at the Dr P.K Charitable Hospital of Belgaum district, South India. Records of all consecutive full term (≥37 weeks of gestation) singleton live births occurring during the period from 1st April-September 31, 2012 was examined to obtain relevant information. Results: A total of 1299 women delivered singleton live births at full term during the stipulated time period. Mean maternal age was 23.28±3.39 years, 53% were primi-gravida and 48.8% were high risk pregnancy. Low birth weight (LBW) was prevalent amongst 19.3% new born. Among the independent significant factors associated with the LBW, primigravida, hypertensive mothers, non cephalic presentation, female baby had 1.31, 1.96, 2.89 and 1.33 times higher odds of delivering/having LBW as against multigravida, normotensive mothers, cephalic presentation and male baby respectively. Conclusions: Primigravida, hypertensive disorders during pregnancy, fetal presentation at delivery and sex of the new born were significantly associated with the LBW. Early identification, monitoring and management of hypertensive disorders during pregnancy eventually reduce the LBWs attributable to hypertension.